Electronic business in developing countries opportunities and challenges - Kamel, Sherif (Hersey, PA Idea Group Pub., 2006)
"This books tackles issues of e-business with a vision to the future on how to bridge these gaps and close down the barriers between the different corners of the world"--Provided by publisher
Electronic business in developing countries : the digitalization of bad practices? / Carlos Ferran, Ricardo Salim -- Role of culture in electronic business diffusion in developing countries / Marwa M. Hafez -- International e-commerce : language, cultural, legal, and infrastructure issues, challenges, and solutions / Magdi N. Kamel -- E-commerce infrastructure and economic impacts in developing countries : case of India / Varadharajan Sridhar, Kala Seetharam Sridhar -- E-marketplace adoption success factors : challenges and opportunities for a small developing country / Andreja Pucihar, Mateja Podlogar -- E-commerce activity, opportunities, and strategies in Latin America / Raul Gouvea, Dante Di Gregorio, Suleiman K. Kassicieh -- Assessing job seekers' acceptance of online recruitment in Egypt / Nahed Azab -- Evolution of telecommunications and mobile communications in India : a synthesis in the transition from electronic to mobile business / Chandana Unnithana, Bardo Fraunholz -- Critical success factors for e-brokerage : an exploratory study in the Brazilian market / Alan Marcelo De Campos Costa, Luiz Antonio Joia -- E-readiness and successful e-commerce diffusion in developing countries : results from a cluster analysis / Alemayehu Molla -- An overview of e-commerce security and critical issues for developing countries / Pierre F. Tiako, Irénée N. Tiako -- Venturing the unexplored : e-readiness assessment of small and medium enterprises in Egypt / Nagla Rizk -- Offshore outsourcing : an e-commerce reality (opportunity for developing countries) / Purva Kansal, Amit Kumar Kaushik -- Adoption and implementation obstacles of e-banking services : an empirical investigation of the Omani banking industry / Abdulwahed Mohammed Khalfan, Abdullah Akbar -- Open sourcing e-learning for developing countries / Ronald M. Lee, Manfred Zielinski, Ramanathan Somasundaram -- Strategic and operational values of e-commerce investments in Jordanian SMEs / Ala M. Abu-Samaha -- E-commerce infrastructure in developing countries / Aladdin Sleem -- An e-commerce longitudinal case study from Ukraine / Murray E. Jennex, Donald L. Amoroso -- E-business in India : early evidence from Indian manufacturing industry / Rajeev Dwivedi, Sushil, K. Momaya -- Challenges and opportunities for information brokers in Brazil : a study of informational needs of Southern-Brazilian enterprises when expanding their businesses / Eusebio Scornavacca, Jr., Joao Luiz Becker, Stuart J. Barnes
Includes bibliographical references and index
Keywords: Electronic commerce -- Developing countries; Electronic commerce -- Developing countries -- Case studies